THE ROLE OF SERIKIN MARKET AS A CENTRE FOR CROSS-BORDER ECONOMIC INTERACTION BETWEEN INDONESIAN AND MALAYSIAN COMMUNITIES: A LITERATURE REVIEW STUDY - Gunawan Widjaja (Adisam Publisher, 2025)
Serikin Market is one of the strategic cross-border economic interaction centres between the Indonesian and Malaysian communities in the border region of West Kalimantan and Sarawak. This study aims to analyse the role and benefits of Serikin Market in supporting cross-border economic, social, and cultural dynamics through a literature review of various relevant sources. The results of the study show that Serikin Market is not only an effective means of distributing goods and services, but also plays an important role in strengthening socio-cultural relations between border residents and encouraging the growth of the micro-economic sector and MSMEs. However, this market also faces significant challenges, such as limited infrastructure, diverse cross-border regulations, and risky informal trading practices. Policy synergy and adaptive management from both governments are needed to maintain the sustainability and optimisation of this market's function as a centre for cross-border economic interaction. This research provides a comprehensive understanding that can serve as a basis for policy-making in border areas.